The Role of Environmental Assumptions in Shaping Requirements Technical Debt - Mounifah Alenazi (Applied Sciences)
Environmental assumptions, which are expectations about a system’s operating context, play a critical yet often underexplored role in the emergence of requirements technical debt (RTD). When these assumptions are incorrect, incomplete, or evolve over time, they can compromise the validity of system requirements and lead to costly rework in later stages of development. This paper investigates how environmental assumptions influence the identification of RTD through the analysis of a real-world case study in the domain of small uncrewed aerial systems (sUASs). A structured qualitative analysis of safety-related requirements and their associated assumptions was conducted to examine how deviations in these assumptions can introduce various forms of RTD. This work addresses a gap in the literature by explicitly focusing on the role of environmental assumptions in RTD identification. A classification framework is proposed, highlighting five distinct types of assumption-driven RTD. This framework serves as a foundation for supporting early detection of debt and improving the sustainability and resilience of software-intensive systems.